Experience of treating Candida auris cases at a general hospital in the state of Qatar - Adila Shaukat (14152062) (2021)
Background and objectives So far there have been no studies on Candida auris in Qatar. This study aimed to describe the clinical spectrum and outcome of C. auris infection in patients admitted to a general hospital in Qatar. Methods We conducted this descriptive observational study in a general hospital in Qatar. We have involved all patients with C. auris infection and colonization admitted to a general hospital from December 2018 to August 2019. Results We identified 13 patients with confirmed C.auris infection/colonization, of which five cases represented an actual C. auris infection, while the remaining eight cases were considered as colonization. The mean age of the patients with infection was 76.6 ± 8.4 years, while the mean age of the patients with colonization was 66.4 ± 24.7 years. Among the individuals clinically infected with C. auris, two had urinary tract infections, one had candidemia, one acquired soft tissue infection, and one had a lower respiratory tract infection. All strains of C. auris were susceptible to echinocandins, flucytosine, and posaconazole while resistance to fluconazole and amphotericin B. Of the patients with C. auris infection who received systemic antifungal therapy, three (60%) died during antifungal therapy. Conclusion Our study showed that C. auris can cause a wide variety of invasive infections, including bloodstream infection, urinary tract infection, skin infection, and lower respiratory tract infections, especially in critically ill patients. In addition, our isolates showed resistance to the most common antifungal agents such as fluconazole and amphotericin B. Other Information Published in: IDCases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.idcr.2020.e01007